Efficacy of PLANT TONIC9 (EOX-SOV) against certain plant pathogenic fungi. (25th March 2022) - Abed-Ashtiani, Farnaz; Arzanlou, Mahdi; Narmani, Abolfazl
Abstract: In this study, PLANT TONIC9 (EOX-SOV) was screened for its in vitro efficacy against some fungal species. PLANT TONIC9 significantly inhibited the mycelial growth and conidial germination of all tested species as compared with untreated control. The highest mycelial growth and conidial germination inhibition percentage was recorded for Monilinia species while the lowest inhibition percentage was recorded for Rosellinia sp. The lowest minimum inhibitory concentration (MIC) value was observed against Monilinia fructigena and Monilinia fructicola followed by Monilinia laxa and Botrytis cinerea . Also the in vivo efficacy of PLANT TONIC9 against M. laxa was investigated. Application of PLANT TONIC9 significantly reduced the severity and incidence of brown rot disease on apple as compared with the control. PLANT TONIC9 treatments were also successful to retain the size, specific gravity, and shelf life of tested fruits and to decrease their spoilage percentage over the experimental period as compared with the control.